The Role of Mayors in Achieving Brunei Darussalam’s Wawasan 2035, Lessons from China - Lee, Brice Tseen Fu; Asihaer, Ayidana; Sims, Juan Pablo (UI Scholars Hub, 2024)
Brunei Darussalam's national vision, WAWASAN 2035, sets forth ambitious goals for the nation's development, emphasizing a centralized governance paradigm. However, the potential of decentralized governance, as exemplified by China's mayor-led districts, offers a compelling model for achieving national aspirations. This research explores the feasibility and potential benefits of introducing mayors in Brunei's districts, drawing insights from China's successful decentralized governance structure. By fostering inter-district competition and allowing for localized policy tailoring, Brunei can enhance its adaptability and responsiveness to local nuances. Drawing from China's experiences, this study provides a comprehensive understanding of how Brunei might optimize its governance structure to more effectively realize the goals enshrined in WAWASAN 2035.